Biological shape analysis by digital curvature - Costa, L. D.; dos Reis, S. F.; Arantes, RAT; Alves, ACR; Mutinari, G. C. (Elsevier B.V., 2004)
This paper reports the novel application of digital curvature as a feature for morphological characterization and classification of landmark shapes. By inheriting several unique features of the continuous curvature, the digital curvature provides invariance to translations, rotations, local shape deformations, and is easily made tolerant to scaling. In addition, the bending energy, a global shape feature, can be directly estimated from the curvature values. The application of these features to analyse patterns of cranial morphological geographic differentiation in the rodent species Thrichomys apereoides has led to encouraging results, indicating a close correspondence between the geographical and morphological distributions. (C) 2003 Pattern Recognition Society. Published by Elsevier Ltd. All rights reserved.
Keywords: shape analysis; digital curvature; morphological and geographic distributions; morphometric analysis; morphological landmark